The Psychological Perception and Usage Behavior of Elderly Users on Smart Health Care Products——A Study of Grounded Theory Based on Text Information - Li Huaqiang; Hu Dongmei (Zhishi guanli luntan, 2023)
[Purpose/Significance] Under the background of the rapid development of the new generation of information technology, the policy supports the smart health care industry, and all kinds of smart health care products are constantly popularized and applied. Exploring the practical issue of elderly users using smart health care products is of great significance for China to carry out smart actions to help the elderly and build a digital inclusive old-age society. [Method/Process] Based on the text information data such as news reports, product reviews and in-depth interviews, this paper adopted the grounded theory method, and formed 3 relational categories, 31 preliminary categories and 69 initial concepts through three-stage coding, and constructed a model of influencing factors of elderly users’ use of smart health care products. [Result/Conclusion] The research showed that the aging degree, product use guidelines and product safety design affect the psychological perception of elderly users, and individual characteristics will adjust their perception. The psychological perception of the elderly includes subjective norms, social support, performance expectations, effort expectations, perceived risks and emotional feelings, which influence the formation of 3 different use behaviors: trial use, persistent use and refusal to use. Finally, some feasible suggestions were put forward from 3 aspects: improving the aging degree of smart health care products, guiding the psychological perception of the elderly users, and enhancing the use skills of the elderly users.